Nutritional Aspects of Juvenile Idiopathic Arthritis: An A to Z for Dietitians - Maria G. Grammatikopoulou; Konstantinos Gkiouras; Vasiliki Syrmou; Tonia Vassilakou; Theodora Simopoulou; Chistina G. Katsiari; Dimitrios G. Goulis; Dimitrios P. Bogdanos (MDPI AG, 2023)
Juvenile idiopathic arthritis (JIA) represents a chronic, autoimmune, rheumatic musculoskeletal disease with a diagnosis before 16 years of age. Chronic arthritis is a common manifestation in all JIA subtypes. The nature of JIA, in combination to its therapy often results in the development of nutrition-, gastrointestinal (GI)- or metabolic-related issues. The most-common therapy-related nutritional issues involve methotrexate (MTX) and glucocorticosteroids (GCC) adverse events. MTX is a folic acid antagonist, thus supplementation with folic acid in required for improving GI side effects and correcting low serum levels. On the other hand, long-term GCC administration is often associated with hyperglycemia, insulin resistance and growth delay. This relationship is further aggravated when more joints are affected and greater doses of GCC are being administered. Apart from stature, body mass index z-scores are also suboptimal in JIA. Other signs of malnutrition include decreased phase angle and muscle mass, especially among patients with polyarthritis JIA. Evidence also points to the existence of an inverse relationship between disease activity and overweight/obesity. Specific dietary patterns, including the anti-inflammatory diet, might confer improvements in selected JIA outcomes, but the level of available research is yet insufficient to draw safe conclusions. The majority of patients exhibit suboptimal vitamin D status; hence, supplementation is recommended. Collectively, the evidence indicates that, due to the age of onset and the complexity of the disease, along with its pharmacotherapy, children with JIA are prone to the development of several nutritional problems, warranting expert monitoring. Vitamin deficiencies, oral and GI-problems limiting dietary intake, faltering growth, overweight and obesity, physical inactivity, or impaired bone health are among the many nutritional issues in JIA requiring dietitian support.